MICROWAVE ASSISTED EXTRACTION OF KETAPANG (Terminalia Catappa) LEAVES AS A GREEN CORROSION INHIBITOR FOR SS400 STEEL IN ACIDIC MEDIUM (HCl) - Adi Renie Happy; Erna Hastuti; Naqiibatin Nadliriyah (Indonesian Physical Review, 2026)
Ketapang (Terminalia Catappa) leaves, which are rich in tannins (11–23%), were investigated as a green corrosion inhibitor for SS400 steel. Tannins were extracted using microwave-assisted extraction (MAE) at 100 W for 0, 1, 3, 5, 7, 9, and 11 minutes. Extracts were characterized using FTIR to identify functional groups and by UV–Vis spectrophotometry to quantify tannin content. Corrosion tests using the weight-loss method showed that the T-7 extract exhibited the lowest corrosion rate of 0.752 mm/y and the highest inhibition efficiency of 92.69%. Optical microscopy revealed reduced surface degradation consistent with the weight-loss results, confirming the protective effect of tannin-rich extracts. Microwave-assisted extraction (MAE) enhanced tannin yield, and the tannin-rich extracts formed protective polyphenolic films that inhibited corrosion via iron–tannin complexation and adsorption. These findings demonstrate that ketapang leaf extract obtained via MAE is an effective, low-cost, and environmentally sustainable inhibitor of steel in acidic environments.